Third-Generation cephalosporins (3GC) and Fluoroquinolones (FQ) Co-Resistance in Extended-Spectrum Beta-Lactamase-Producing Escherichia coli (ESBL-Ec) from Clinical and Community Isolates - Febrianti, Tati; Puspandari, Nelly; Karuniawati, Anis (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
The growing AMR issue affects the current antimicrobial therapy recommendations, particularly for broad-spectrum antibiotics, like third-generation cephalosporins (3GC) and fluoroquinolones (FQ). Actually, the inappropriate use of both antibiotics in clinical and community settings increase the resistance of extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-Ec). Although ESBL-Ec is used as a surveillance indicator of bacterial resistance, but currently studies related to 3GC-FQ co-resistance among clinical and community (including human and wastewater samples) based ESBL-Ec isolation, have not been widely carried out. The objective of this study was to analyze the possibility and mechanism of 3GC-FQ co-resistance among ESBL-Ec, in human clinical and communal isolates from previous published research. Out of 257 articles screened, four studies in accordance with our study are included in the analysis. The result indicated that ESBL-Ec derived from all sample sources had 3GC-FQ co-resistance. According to two studies reviewed, blaCTX-M was the most predominant ESBL gene, while the FQ-associated resistant gene dominated by qnr family genes. Resistant genes and co-resistant ESBL-Ec can be spread rapidly through plasmids.